Civility, barbarism, and the evolution of international humanitarian law who do the laws of war protect? - Killingsworth, Matt; McCormack, Timothy L. H. (Cambridge New York Cambridge University Press, 2023)
The history of conflict is replete with examples of exclusions from protections designed to moderate warfare. This edited volume explores how protections in modern warfare might be informed by notions of 'civility' and 'barbarism', and asks if only those deemed to be civilised are afforded protections prescribed by the laws of war"--
Civility, barbarism, and the evolution of international humanitarian law : who do the laws of war protect? : introduction / Matt Killingsworth and Tim McCormack -- Sieges and the laws of war in Europe's long eighteenth century long / Gavin Daly -- All's fair in love and war, or The limits of the limitations : juridification of warfare and its revocation by military necessity / Miloš Vec -- Cultivating humanitarianism : moral sentiment and international humanitarian law in the civilizing process / Richard Devetak -- Limits to the scope of humanity as a constraint on the conduct of war / Tim McCormack, Siobhain Galea, and Daniel Westbury -- The state, civility, and international humanitarian law / Matt Killingsworth -- Operationalising distinction in South Sudan : humanitarian decision-making about military asset use / Rebecca Sutton -- Private military and security companies and international humanitarian law : the Montreux document / Rebecca Shaw -- Protecting warfighters from superfluous injury and unnecessary suffering / Rain Liivoja -- Blurring the lines : how are female child soldiers protected by the laws of war? / Rosemary Grey -- A step back to take a step forward : the future of justice in conflict / Mark Kersten.
Includes bibliographical references and index.
Keywords: Civilization; Humanitarian law; War (International law)